Keefektifan Telenomus remus (Nixon) (Hymenoptera: Scelionidae) dalam mengendalikan hama tanaman bawang daun Spodoptera exigua Hübner (Lepidoptera: Noctuidae) - Buchori, Damayanti; Herawati, Erna Dwi; Sari, Adha (Perhimpunan Entomologi Indonesia, 2008)
The objective of this research is to study the effectiveness of T. remus as biocontrol agent for S. exigua. The study was conducted by releasing a set of T. remus females on potted onion plants that have been attacked by S. exigua. Three different parasitism level was artificially created by releasing different numbers of females: low rate parasitism (release of 4 adult females), moderate parasitism (7 females) and high parasitism level (11 females). The result of this study showed that T. remus is effective to control S. exigua population. Up to 48.2% of S. exigua. population was able to be suppressed by the high parasitism level. Rate of parasitisation was more when more adult female T. remus was released. Release of 11 adult female of T. remus can increase the population level of the parasitoid up to 24.1 times than the initial population. This express that T. remus is a mortality factor which can regulate the population of S. exigua. However, the succesfull parasitisation of T. remus is also dependent on environmental factors such as temperature, humidity, food, and host suitability.